Researching the recovery of locomotor activity after traumatic conditions of the lower limb - Atanas Drumev; Danelina Vacheva (Journal of Biomedical & Clinical Research)
The ability of living organisms to navigate their environment is essential for survival. In scientific literature, this ability is known as locomotion, with walking being the primary mode of human movement. Our focus on the potential for independent movement within the environment arises from the high incidence of lower limb injuries and the significant number of patients requiring assistive devices to improve their walking ability, which is why we are conducting this review. The gait cycle begins with the stance phase, marked by heel contact, and consists of five subphases: initial contact, loading response, mid-stance, terminal stance, and pre-swing. The subsequent swing phase includes three subphases: initial, mid, and terminal swing. Key characteristics for assessing gait parameters are categorised into spatial and temporal indicators. Spatial indicators include stride length, step length, stride width, and foot angle, while temporal indicators encompass stance and swing phases, cadence, stride and step time, single and double support time, and speed. Human gait analysis has been done using numerous research methods, with traditional approaches being semi-subjective. Recent technological advancements have led to devices for objective evaluation, classified into non-wearable and wearable sensors. Our research focused on gait parameters to monitor recovery in patients with lower limb injuries and evaluated the G-WALK model, a wearable inertial sensor device which effectively registers spatial and temporal gait parameters.Numerous unanswered questions about gait recovery after lower extremity trauma motivated this review.